MAKANAN TRADISIONAL, BAHASA, DAN REVOLUSI INDUSTRI 4.0 - Budi Agung Sudarmanto; Abu Salim (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The era of Industrial Revolution 4.0 was a further era of the Third Industrial Revolution that stimulated the advancement of science and technology with Internet of Things (IoT) and its supporting technology to become the backbone of Cyber-Physical Systems (CPS) and advanced machines were used as promoters to optimize the circuit production. Such progress crosses organizational and territorial boundaries, which consist of agility, intelligence, and also networking. Traditional South Sumatra food as a decent product to be introduced to the public and compete in the industrial world (especially culinary). As a local product, you need language support tools as intermediaries. Local languages need to be accommodated in the national language (Indonesian), so that it will be easier to make understanding in foreign languages (for example, English).